Vaginal microbiota of American Indian women and associations with measures of psychosocial stress. - Joanna-Lynn C Borgogna; Michael Anastario; Paula Firemoon; Elizabeth Rink; Adriann Ricker; Jacques Ravel; Rebecca M Brotman; Carl J Yeoman (PLoS ONE)
Molecular-bacterial vaginosis (BV) is characterized by low levels of vaginal Lactobacillus species and is associated with higher risk of sexually transmitted infections (STI). Perceived psychosocial stress is associated with increased severity and persistence of infections, including STIs. American Indians have the highest rates of stress and high rates of STIs. The prevalence of molecular-BV among American Indian women is unknown. We sought to evaluate measures of psychosocial stress, such as historic loss (a multigenerational factor involving slavery, forced removal from one's land, legally ratified race-based segregation, and contemporary discrimination) and their association with the vaginal microbiota and specific metabolites associated with BV, in 70 Northwestern Plains American Indian women. Demographics, perceived psychosocial stressors, sexual practices, and known BV risk factors were assessed using a modified version of the American Indian Service Utilization, Psychiatric Epidemiology, Risk and Protective Factors Project survey. Self-collected mid-vaginal swabs were profiled for bacterial composition by 16S rRNA gene amplicon sequencing and metabolites quantified by targeted liquid-chromatography mass spectrometry. Sixty-six percent of the participants were classified as having molecular-BV, with the rest being either dominated by L. crispatus (10%) or L. iners (24%). High levels of lifetime trauma were associated with higher odds of having molecular-BV (adjusted Odds Ratio (aOR): 2.5, 95% Credible Interval (CrI): 1.1-5.3). Measures of psychosocial stress, including historic loss and historic loss associated symptoms, were significantly associated with lifestyle and behavioral practices. Higher scores of lifetime trauma were associated with increased concentrations of spermine (aFC: 3.3, 95% CrI: 1.2-9.2). Historic loss associated symptoms and biogenic amines were the major correlates of molecular-BV. Historical loss associated symptoms and lifetime trauma are potentially important underlying factors associated with BV.